Equipping clinical leaders for system and service improvements in quality and safety: an Australian experience - Sandra G. Leggat; Anne Smyth; Cathy Balding; Iain McAlpine (Elsevier, 2016)
Abstract Objective: To develop clinical leadership among health professionals working in public sector organisations to improve their skills in ensuring high quality and safe health services. Methods: A longitudinal pre‐post‐intervention mixed methods study that included 60 health professionals working in one state in Australia. Results: The program was successful in the development of clinical leaders. Conclusions: An interdisciplinary, inter‐sectoral leadership development program involving health professionals from metropolitan, regional and rural areas can be successful in developing knowledge, skills and competencies among these health professionals in health service quality and safety. Implications: Health professionals can participate in a development program to enhance their clinical leadership skills. While this was a post‐qualification course, targeting experienced health professionals, the learnings could be applied to pre‐qualification education of health professionals.